2015
DOI: 10.1080/15287394.2014.991466
|View full text |Cite
|
Sign up to set email alerts
|

Picocyanobacteria From a Clade of MarineCyanobiumRevealed Bioactive Potential Against Microalgae, Bacteria, and Marine Invertebrates

Abstract: The production of bioactive compounds either toxic or with pharmacological applications by cyanobacteria is well established. However, picoplanktonic forms within this group of organisms have rarely been studied in this context. In this study, the toxicological potential of picocyanobacteria from a clade of marine Cyanobium strains isolated from the Portuguese coast was examined using different biological models. First, strains were identified by applying morphological and molecular approaches and cultured und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Synechococcales bacteria contribute to more than the 25% of the global photosynthesis (Fuhrman et al, 2015). Cyanobium PCC-6307 is characterized by strong bioactive compounds against the growth of other microorganisms (Costa et al, 2015) and may influence the freshwater communities. The Microtrichales, Micrococcales and Frankiales of the phylum Actinobacteria may produce also bioactive compounds and help to remineralize recalcitrant organic matter.…”
Section: Bacterial Community Composition and Potential Roles Across Tmentioning
confidence: 99%
“…Synechococcales bacteria contribute to more than the 25% of the global photosynthesis (Fuhrman et al, 2015). Cyanobium PCC-6307 is characterized by strong bioactive compounds against the growth of other microorganisms (Costa et al, 2015) and may influence the freshwater communities. The Microtrichales, Micrococcales and Frankiales of the phylum Actinobacteria may produce also bioactive compounds and help to remineralize recalcitrant organic matter.…”
Section: Bacterial Community Composition and Potential Roles Across Tmentioning
confidence: 99%
“…Picocyanobacteria play an important role in aquatic ecosystems (Beardall 2008;Callieri 2010;Costa et al 2015;Worden and Wilken 2016) but little is known about their allelopathic activity again coexisting microalgae. In previous works, we demonstrated the allelopathic effect of Synechococcus sp.…”
Section: Introductionmentioning
confidence: 99%
“…The picocyanobacteria Synechococcus sp., Synechocystis sp., and Cyanobium sp. displayed a negative effect on the survival of selected animals [29][30][31][32]. These results obtained indicated that freshwater picocyanobacteria may serve as a potential source of interesting bioactive compounds, whose mode of action on target organisms requires detailed investigation.…”
Section: Introductionmentioning
confidence: 80%